2022
DOI: 10.1038/s41467-022-29261-0
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling RCOR1 as a rheostat at transcriptionally permissive chromatin

Abstract: RCOR1 is a known transcription repressor that recruits and positions LSD1 and HDAC1/2 on chromatin to erase histone methylation and acetylation. However, there is currently an incomplete understanding of RCOR1’s range of localization and function. Here, we probe RCOR1’s distribution on a genome-wide scale and unexpectedly find that RCOR1 is predominantly associated with transcriptionally active genes. Biochemical analysis reveals that RCOR1 associates with RNA Polymerase II (POL-II) during transcription and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…As one of the members of sodium-calcium exchangers, SLC8A2 has been previously evidenced as a nuclear translocation regulator of HIF1A [35], which was signi cantly down-regulated upon SLC8A2 overexpression [36]. Our study indicated that SLC8A2 acts upstream of multiple hypoxia and/ or altitudesensitive miR targets, like RCOR1 (a transcription rheostat essential for normal myeloerythroid lineage differentiation) [37,38]; PRDM1 and LDB1(both are involved in high-altitude adaptation) [39,40]; and CASP3 (a member of hypoxia-activated mitochondrial apoptosis pathway) [41]. We noticed that, both hsa-miR-133a-3p and hsa-miR-133b-3p mediate the signals from SLC8A2 or DIP2B to SLC4A1, a biomarker of AMS, which was correlated with various AMS symptoms and plays important roles in CO 2 gas transport in erythrocytes [42].…”
Section: Discussionmentioning
confidence: 51%
“…As one of the members of sodium-calcium exchangers, SLC8A2 has been previously evidenced as a nuclear translocation regulator of HIF1A [35], which was signi cantly down-regulated upon SLC8A2 overexpression [36]. Our study indicated that SLC8A2 acts upstream of multiple hypoxia and/ or altitudesensitive miR targets, like RCOR1 (a transcription rheostat essential for normal myeloerythroid lineage differentiation) [37,38]; PRDM1 and LDB1(both are involved in high-altitude adaptation) [39,40]; and CASP3 (a member of hypoxia-activated mitochondrial apoptosis pathway) [41]. We noticed that, both hsa-miR-133a-3p and hsa-miR-133b-3p mediate the signals from SLC8A2 or DIP2B to SLC4A1, a biomarker of AMS, which was correlated with various AMS symptoms and plays important roles in CO 2 gas transport in erythrocytes [42].…”
Section: Discussionmentioning
confidence: 51%
“…As one of the sodium-calcium exchangers, SLC8A2 has been previously shown to be a nuclear translocation regulator of HIF1A 37 , which was significantly downregulated upon SLC8A2 overexpression 38 . Our study indicated that SLC8A2 acts upstream of multiple hypoxia-and/or altitude-sensitive miR targets, such as RCOR1 (a transcription rheostat essential for normal myeloerythroid lineage differentiation) 39,40 , PRDM1 and LDB1 (both are involved in high-altitude adaptation) 41,42 , and CASP3 (a member of the hypoxia-activated mitochondrial apoptosis pathway) 43 . We noticed that both www.nature.com/scientificreports/ hsa-miR-133a-3p and hsa-miR-133b-3p mediate the signals from SLC8A2 or DIP2B to SLC4A1, a biomarker of AMS, which was correlated with various AMS symptoms and plays important roles in CO 2 gas transport in erythrocytes 44 .…”
Section: Discussionmentioning
confidence: 79%
“…These, on the first sight, contradictory observations could be explained with HMG20A acting as rheostat and thereby fine-tuning the expression of highly transcribed genes. Such a function has been previously described for the NuRD complex 43 and RCOR1 of the BHC/CoREST complex 44 . It is therefore tempting to speculate that HMG20A – among other functional outputs – works together with these complexes to dampen transcription of genes during differentiation.…”
Section: Discussionmentioning
confidence: 80%